Gender Responsive Values in Fiqh Subjects: Concepts and Practices in Madrasah Ibtidaiyah Levels - Musyarrafah Sulaiman Kurdi (Journal of Gender and Millennium Development Studies, 2024)
Unconscious gender discrimination from the education curriculum has more or less formed a pattern of understanding of doctrines that strengthen the legitimacy of patriarchy. Many facts show various gender injustice treatments in society. The purpose of this study is to analyze gender-responsive values in fiqh subjects and their influence on learning in Madrasah Ibtidaiyah schools. The research method uses the critical discourse analysis method. Data sources are important documents about fiqh learning policies in Madrasah Ibtidaiyah schools and scientific journals as supporters. Data analysis uses text analysis. Fiqh in Madrasah Ibtidaiyah School that is studied contains two main elements, namely related to worship and related to muamalah. The conclusion of the research shows that the Fiqh curriculum at Madrasah Ibtidaiyah School must optimize the synergy of intellectual aspects, attitudinal aspects, and aspects of amaliyah skills in core skills and basic skills. The contribution of this research is as a source of knowledge information both theoretically and practically regarding gender responsive values in Fiqh subjects at school.